2021
DOI: 10.1002/ece3.7124
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenically modified habitats favor bigger and bolder lizards

Abstract: Anthropogenic activities often create distinctive but discontinuously distributed habitat patches with abundant food but high risk of predation. Such sites can be most effectively utilized by individuals with specific behaviors and morphologies. Thus, a widespread species that contains a diversity of sizes and behavioral types may be pre‐adapted to exploiting such hotspots. In eastern Australia, the giant (to >2 m) lizard Varanus varius (lace monitor) utilizes both disturbed (campground) and undisturbed (bushl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Similarly, in areas with high human population density, animals can become acclimated to people and flee at shorter distances during flight tests ( Ekanayake et al, 2022 ). In some cases, influences of human activity on results of flight tests can be applied to understanding human-wildlife coexistence and can provide insights into behavioral responses to environmental changes caused by anthropogenic activity ( Pettit et al, 2021 ; Mikula et al, 2023 ).…”
Section: Temperamentmentioning
confidence: 99%
“…Similarly, in areas with high human population density, animals can become acclimated to people and flee at shorter distances during flight tests ( Ekanayake et al, 2022 ). In some cases, influences of human activity on results of flight tests can be applied to understanding human-wildlife coexistence and can provide insights into behavioral responses to environmental changes caused by anthropogenic activity ( Pettit et al, 2021 ; Mikula et al, 2023 ).…”
Section: Temperamentmentioning
confidence: 99%
“…Moreover, many animals in human‐modified habitats show higher boldness and risk‐taking behaviours than their conspecifics in natural habitats (e.g. Baxter‐Gilbert et al., 2019; Ducatez et al., 2017; Pettit et al., 2021). In addition, reliance on artificial human food sources may also increase individual aggression, which might result in injuries (Knight, 2009; Milner et al., 2014), promote disease transmission (Becker et al., 2015; Murray et al., 2016; Plowright et al., 2011) and create behavioural barriers preventing population mixing, causing inbreeding and reduced genetic diversity (Berger‐Tal & Saltz, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We measured the owl tolerance to a possible predator using the "Flight Initiation Distance" (FID), a widespread and well-established method (Fig. 1C, for more details, see Stankowich & Blumstein 2005, Price 2008, Møller 2010, Tätte et al 2018, Pettit et al 2021. We thoroughly searched for owl nests within the study area (~70 hours) and, at each nest found, S1).…”
mentioning
confidence: 99%